2019
DOI: 10.2185/jrm.3001
|View full text |Cite
|
Sign up to set email alerts
|

A case of laparoscopic fenestration surgery for pelvic lymphocele occurring after laparoscopic radical prostatectomy

Abstract: A 76-year-old Japanese man visited a nearby medical clinic complaining of abdominal distention. He had undergone extraperitoneal laparoscopic prostatectomy at our institution 5 months before the onset of abdominal distention. An imaging study revealed a large cystic lesion, and biochemical examination of a sample obtained via cyst puncture led to a diagnosis of lymphocele. As the lymphocele was resistant to puncture, drainage, and sclerotherapy with minomycin, laparoscopic fenestration was performed. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…3,4 Laparoscopic marsupialization is also an option. 5 To identify and embolize lymph leakage, lymphangiography using indocyanine green or ethiodized oil is effective. 6,7 A systematic review 8 showed proportions of successful interventions for percutaneous catheter drainage, percutaneous catheter drainage with the addition of sclerotherapy, and embolization: 0.612 (95% confidence interval [CI]: 0.490-0.722), 0.890 (95% CI: 0.781-0.948), and 0.922 (95% CI: 0.731-0.981), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Laparoscopic marsupialization is also an option. 5 To identify and embolize lymph leakage, lymphangiography using indocyanine green or ethiodized oil is effective. 6,7 A systematic review 8 showed proportions of successful interventions for percutaneous catheter drainage, percutaneous catheter drainage with the addition of sclerotherapy, and embolization: 0.612 (95% confidence interval [CI]: 0.490-0.722), 0.890 (95% CI: 0.781-0.948), and 0.922 (95% CI: 0.731-0.981), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…When it is refractory to conservative treatment, we need to consider surgical therapies, such as embolization of the leaking lymphatic ducts, lymphatic microsurgery (lymphatic ligation, lymphovenous or lympholymphatic anastomosis) 3,4 . Laparoscopic marsupialization is also an option 5 . To identify and embolize lymph leakage, lymphangiography using indocyanine green or ethiodized oil is effective 6,7 .…”
Section: Discussionmentioning
confidence: 99%